HIV Nef- and Notch1-dependent Endocytosis of ADAM17 Induces Vesicular TNF Secretion in Chronic HIV Infection - Ostalecki, Christian; Wittki, Sebastian; Lee, Jung-Hyun; Geist, Miriam M.; Tibroni, Nadine; Harrer, Thomas; Schuler, Gerold; Fackler, Oliver T.; Baur, Andreas (EBioMedicine, 2016)
Tumor necrosis factor (TNF) is a key cytokine in HIV replication and pathogenesis. For reasons that are not entirely clear, the cytokine remains upregulated despite anti-retroviral therapy (ART). Here we demonstrate that HIV Nef induces an alternative TNF secretion mechanism that remains active in chronic infection. Ingestion of Nef-containing plasma extracellular vesicles (pEV) from ART patients by primary immune cells, but also Nef expression, induced intracellular proTNF cleavage and secretion of vesicular TNF endosomes. Key event was the Nef-mediated routing of the TNF-converting enzyme ADAM17 into Rab4+ early endosomes and the Rab27+ secretory pathway. Analysis of lymph-node tissue by multi-epitope-ligand-cartography (MELC) confirmed a vesicular TNF secretion phenotype that co-localized with persistent Nef expression, and implicated Notch1 as an essential co-factor. Surprisingly Notch1 had no transcriptional effect but was required for the endosomal trafficking of ADAM17. We conclude that Nef expression and Nef-containing pEV mobilize TNF from endosomal compartments in acute and chronic infection.
EVALuna2:13372